Mengevaluasi Berbagai Teknik Storytelling untuk Pendidikan Anak Usia Dini: Sebuah Studi Literatur - Khusnul Khotimah; Ratih Permata Sari (Universitas Nusantara PGRI Kediri, 2025)
This study aims to evaluate various storytelling techniques in supporting early childhood development. The research employed a literature review method by examining studies published between 2019 and 2024 on the use of storytelling in early childhood education. The analysis techniques included findings synthesis and critical analysis of various studies. The results revealed that visual media-based storytelling techniques, such as pictures and hand puppets, effectively enhance children’s language skills and vocabulary. Moreover, digital techniques such as interactive storytelling and audiovisual media create more engaging and interactive learning experiences, significantly improving children’s social-emotional and cognitive skills. Therefore, the selection of storytelling techniques should be adjusted according to learning needs and contexts for optimal results.